2016
DOI: 10.17323/1814-9545-2016-2-208-228
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Apprenticeship of Observation on Teachers Attitudes towards Active Learning Instruction

Abstract: Abstract. Active learning instruction is promoted by the most recent version of the National Program for the Development of Education in Kazakhstan as it is believed to provide more meaningful learning and deeper understanding compared to traditional instruction. In order to achieve greater utilization of the instructional approach at schools, teachers must be aware of active learning techniques and know how to use them. This paper studies whether 'apprenticeship of observation' during a graduate course using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Using purposive sampling, the larger study involved 18 novice English teachers (nets henceforth; 14 women, 4 men) aged from 23 to 35 and working in different educational contexts in the Santiago Metropolitan Region of Chile. The study focused on novice teachers, expecting that memories of their plle would be fresher than those of more experienced teachers who have had more opportunities for reflection (Kuzhabekova & Zhaparova, 2016). Teachers from the three types of schools (public, private-subsidised, and private) were included to provide a more complete view of the influence of past experiences on different teaching contexts.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using purposive sampling, the larger study involved 18 novice English teachers (nets henceforth; 14 women, 4 men) aged from 23 to 35 and working in different educational contexts in the Santiago Metropolitan Region of Chile. The study focused on novice teachers, expecting that memories of their plle would be fresher than those of more experienced teachers who have had more opportunities for reflection (Kuzhabekova & Zhaparova, 2016). Teachers from the three types of schools (public, private-subsidised, and private) were included to provide a more complete view of the influence of past experiences on different teaching contexts.…”
Section: Participantsmentioning
confidence: 99%
“…This influence has been found to affect the views and practices of English as a second or foreign language (esl/efl) teachers throughout their careers (Barahona, 2014;S. Borg, 2003;Kuzhabekova & Zhaparova, 2016). In fact, it has been found to be even more influential than teacher education programmes, which may explain the "weak effect" that esl/efl teacher education has been found to have on student teachers (M. Borg, 2005;Johnson, 1994;Korthagen, 2010;Zeichner & Tabachnick, 1981).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is paramount to consider that the way teachers teach is highly connected to the way they learned as students. In fact, research (KUZHABEKOVA; ZHAPAROVA, 2016;JOHN, 1996;BALL, 1990) has shown that teachers develop and hold implicit theories about "their pupil, about the subject matter they teach and about their roles and responsibilities and about how they act" (JOHN, 1996, p. 90). In this sense, experience and instruction walk hand in hand in the process of becoming a teacher.…”
Section: Review Of Literaturementioning
confidence: 99%